Kurikulum Merdeka : Tantangan Pembelajaran IPS Pada Siswa Sekolah Dasar Studi Kasus Di SD Negeri 26 Kota Ternate - Rahmat Muhdar; Marlina , Yetni (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
The aim of carrying out this research is to describe planning, implementation, supporting and inhibiting factors, as well as solutions in differentiated learning in the Merdeka curriculum in science and science subjects at SDN 26 Ternate City. This research uses qualitative research with a case study design. Data was collected through interviews, observation and documentation. The subjects of this research consisted of the school principal, class IV teacher, and three class IV students. Test the validity of the data using triangulation of techniques and sources. Then the data was analyzed using the Miles and Hubermen technique with three stages, namely data reduction, data presentation, and drawing conclusions. The results obtained were that teachers made learning plans by mapping learning needs through diagnostic assessments and then creating teaching modules based on the results of the mapping. It is known that class IV students consist of visual, auditory and kinesthetic learning styles. In its application, teachers carry out learning differentiation of content, processes and products. Supporting factors come from enthusiastic students, a pleasant learning atmosphere, students feeling safe and comfortable, and adequate infrastructure. Meanwhile, the main inhibiting factor in learning is that it takes longer. The solution taken by the principal and teachers is to reflect together every week.